National Identity and Sociocultural Security - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The contemporary tendencies of globalization, political and civilization challenges and the attack of mass culture lead to chaos. As a result, nation as a historical subject providing the cultural diversity, finds itself in a peril. Proceeding from the social-philosophical analysis of national identity the author comes to the conclusion that the way of existing of the Armenians as a special ethnoand sociocultural system has permanently been balanced by the moderate contradiction of the individuality and the collectivity. The sociocultural imperative of maintaining the national identity is such a combination of collective-irrational and individual-rational philosophies of existence which aims at pouring into the international ordered life, definitely ordering liberal-democratic mechanisms of functional bonds and interdependences.